Field notes contributed by Raymond L. Cummins, June 3, 1979 - Cummins, Raymond L.et al (1979)
Spring report of birds found primarily in Pocahontas County contributed by Raymond L. Cummins, June 3, 1979. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1979. Contex - flatbed